Social Solidarity in The Moment of The Prophet's Maulid: A Living Hadith Study on The Weh-Wehan Tradition during The Celebration of The Prophet's Maulid in Kaliwungu Community - Mohamad Nuryansah; Muhammad Izzul Haq (Islamika Inside: Jurnal Keislaman dan Humaniora, 2023)
Kaliwungu is a sub-district in Kendal Regency, Central Java Province. This area has various local wisdom and traditions that have been carried out for generations, including the "weh-wehan" tradition. The weh-wehan ceremony commemorates the maulid of the Prophet Muhammad Saw. as a gratitude for the birth of the role model and messenger of Allah Swt. This paper examines the weh-wehan tradition in Kaliwungu using a living hadith approach and a functional, structural approach. The results show that the "weh-wehan" tradition is an activity of giving food or goods to each other. Weh-wehan comes from the Javanese language, which means giving each other. The weh-wehan ceremony is held every 11th of Rabiul Awal and is carried out by exchanging food or goods. This tradition contains elements of social solidarity full of meaning: sharing enjoyment, fostering mutual respect and affection, strengthening brotherhood, and sharing happiness.